Implementation of pharmaceutical development using multivariate analysis of multi-criteria optimization on the example of the stage of purification of oligohexamethyleneguanidine hydrosuccinate - D. O. Shatalov; K. N. Trachuk; A. V. Aydakova; D. A. Akhmedova; I. S. Ivanov; D. S. Minenkov; I. Yu. Blazhevich; S. A. Kedik (Тонкие химические технологии)
Objectives. The study set out to use mathematical modeling, in particular the method of multifactorial analysis of multicriteria optimization (MAMO), in the development of a pharmaceutical product.Methods. After carrying out experimental tests based on the proposed algorithmic sequence, the obtained data were interpreted using MAMO.Results. The possibility of using MAMO to solve the applied problem of purifying oligohexamethyleneguanidine hydrosuccinate (OHMG-HS), considered as a pharmaceutical precursor for the creation of medicines, was demonstrated.Conclusions. The expediency of using the proposed algorithm as a tool for pharmaceutical development is substantiated by identifying dependencies of the influence of purification conditions on the final content of admixtures in the target product.